Curriculum frameworks from an “Ethical-Aesthetic” perspective for the development of environmental culture - Melo Romero, Andrea del Pilar (2024)
The article Curricular Pathways from an Aesthetic Ethics for the Formation of an Environmental Culture is part of the preliminary results of a research conducted with high school students in Bogota, Colombia, which works on ethics-aesthetics as an alternative proposal from the construction of a Latin American environmental thinking. The first part of the article explains what ethics-aesthetics refers to; in the second part of the article, the methodological design of the research is explained; in the third part, the environmental values that can be worked from ethics-aesthetics and how they are perceived within an environmental forum developed with the learning community are discussed; finally, the article concludes with the findings.